Avanços e desafios da educação superior indígena: um olhar sobre os indígenas da UFOPA oriundos de Jacareacanga-Pa - (:unkn) unknown (Universidade Federal do Oeste do Pará, 2021)
The present work portrays the theme Advances and Challenges of Indigenous Higher Education with a look at UFOPA indigenous people from the municipality of Jacareacanga - Pará, the presence of indigenous people in higher education increased significantly after the implementation by the state and federal government of action policies affirmative, such policies are the result of the struggles of these peoples. With this principle in mind, this work aims to investigate and identify the main advances and challenges experienced by indigenous scholars from UFOPA and what are their future perspectives from their professional / academic training because we understand that they can contribute to their villages outside of it, for example, in political party participation or in social movements. The methodological steps to achieve the proposed objectives, a research classified as exploratory was carried out, the research also used the following methods: bibliographic, documentary and interview by digital platform. The research shows the importance of the Jacareacanga indigenous people and the possibility of contributing to the cultural and, also economic growth of the municipality through occupation in some public agency or through political party participation.
Keywords: Educação Superior; Indígena; Participação; CNPQ:: CIÊNCIAS SOCIAIS APLICADAS